2022
DOI: 10.1186/s40814-022-01200-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and preliminary effects of exercise interventions on plasma biomarkers of Alzheimer’s disease in the FIT-AD trial: a randomized pilot study in older adults with Alzheimer’s dementia

Abstract: Background Alzheimer’s disease (AD) biomarkers have provided a unique opportunity to understand AD pathogenesis and monitor treatment responses. However, exercise trials show mixed effects on imagining and cerebrospinal fluid biomarkers of AD. The feasibility and effects of exercise on plasma biomarkers remain unknown. The primary objective of this study was to examine the feasibility of recruitment, retention, and blood sample collection in community-dwelling older adults with mild-to-moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Studies conducted on Aβ species, including middleaged and older men and women with normal cognitive status, mild cognitive impairment or AD indicated no significant effect of exercise interventions, lasting from 8 weeks to 1 year and including 3 to 5 sessions of 45 to 60 min weekly, on either blood (14)(15)(16)(17)(18), CSF (19) or brain (20)(21)(22) amyloid levels, compared to control groups. However, subgroup analyses demonstrated that in APOE-ε4 allele carriers with AD, an increase in CSF Aβ40 was observed in inactive controls after 16 weeks of follow-up while the carriers from the exercise group maintained their baseline concentrations (19).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies conducted on Aβ species, including middleaged and older men and women with normal cognitive status, mild cognitive impairment or AD indicated no significant effect of exercise interventions, lasting from 8 weeks to 1 year and including 3 to 5 sessions of 45 to 60 min weekly, on either blood (14)(15)(16)(17)(18), CSF (19) or brain (20)(21)(22) amyloid levels, compared to control groups. However, subgroup analyses demonstrated that in APOE-ε4 allele carriers with AD, an increase in CSF Aβ40 was observed in inactive controls after 16 weeks of follow-up while the carriers from the exercise group maintained their baseline concentrations (19).…”
Section: Resultsmentioning
confidence: 92%
“…Likewise, 6 months of cycling exercise had no impact on the blood levels of phosphorylated tau 181 in cognitively healthy older adults ( 18 ). Furthermore, in older adults with AD, neither 16 ( 19 ) or 24 weeks ( 17 ) of aerobic exercise impacted the concentrations of total and phosphorylated tau proteins measured in the CSF or in the blood.…”
Section: Resultsmentioning
confidence: 99%
“…The modifiable effects of physical activity are not only restricted to physiological aging, but also continue in people with dementia, as it is shown recently in people with Alzheimer's disease, via regulating some of the disease biomarkers. That is, amyloid and total and phosphorylated (p181) tau protein in plasma (Yu et al, 2022 ). The findings of the studies in this collection collectively suggest that regular exercise is associated with improved white matter microstructural integrity, regardless of the exercise type, age, gender.…”
mentioning
confidence: 99%